Moldovan policy in the context of the conflict between Russia and the West - S. S. Zhiltsov (Проблемы постсоветского пространства, 2025)
Modern Moldovan policy considers the geopolitical realities associated primarily with the military conflict in Ukraine. In the context of Russia’s Special Military Operation, the Moldovan side has intensified its foreign policy, which is aimed at expanding cooperation with the Western states. The decision of Ukraine to stop the transit of Russian gas through its territory has given Chisinau an additional leverage over Transnistria, which depends on gas imports. The Moldovan authorities have two goals. The first one is to exert pressure on Transnistria in order to realize the strategy of reducing the autonomy of Tiraspol. The second one is to implement plans for the reintegration of the two parts of the country. Economic and political pressure on Transnistria is carried out with the support of the EU, which backed Kiev in cancelling the transit of Russian gas and does not interfere in the interaction between Chisinau and Tiraspol. Additionally, the issue of gas supplies plays a big role in the relations between Moldova and Transnistria, as both Chisinau and the unrecognized republic depend on gas. Until the end of 2024, Moldova received electricity generated in Transnistria on the basis of cheap Russian gas. Furthermore, since the beginning of 2025, Moldova has aggravated relations with Gagauzia, whose position regarding the internal and external political courses of the country causes dissatisfaction in Chisinau. The article concludes that the strategy of the Moldovan authorities has led to the growth of domestic political conflict and increased geopolitical tension in the Western part of the post-Soviet area. the Eurasian area has a long-term basis and meets the interests of Moscow.